Analysis of Amir’s Characterizations and His Regret in Novel The Kite Runner by Khaled Hosseini - Kusumawati, Irma (Program Studi Tadris Bahasa Inggris, Fakultas Tarbiyah, IAIN Kediri, 2024)
The purpose of this study is to find out how Amir’s characterization undergoes a transformation, marked by a profound sense of guilt toward his servant, as he reflects on the reasons behind his regret. This research is descriptive qualitative where the data in this study is novel “The Kite Runner by Khaled Hosseini”. This study takes data from two characters as a main focus of this novel from monologue and dialogue. The characters that are packaged beautifully by the author attract readers to know how the story of each character looks. The data were analyzed with following steps such as analyzing the data, compiling, defining, and classifying the data to find out why Amir's characteristics tends to feel guilty. The result of the research is Amir's characterizations that he is a good and smart boy. However, several external and internal factors change him to be a selfish boy and a liar. The reason why he feels guilty is when he lets his servant and also his best friend Hassan gets hurt by three bad boys at the end of the kite race. This can be a lesson for parents and teachers not to charge children with something they do not like. Moreover, every child has each ability and expertise, so that children can grow up to be good and talented children as well as good characteristics are important and good values.